Research on the Vatsonga people of Southern Africa: A reflection on a case study - Samuel Lisenga Simbine; Liana Le Roux; Noel Garikai Muridzo (National Association of Social Workers-Zimbabwe, 2023)
For decades, African researchers relied on Eurocentric concepts, models, philosophies, ethics, designs, and methods ingrained in the European research literature. The indiscriminate use of Eurocentric concepts to conceive African research is not sustainable given the uniqueness of African cultures. This situation gives impetus to the call for the development of a way of conducting research that is more suited to indigenous African contexts. The paper contains a reflection on the researchers’ past research experiences within African socio-cultural contexts. We aim to share our experiences on a research study that we conducted in Zimbabwe with the Vatsonga of Southern Africa; one of the ethnic groups that adopt an Afrocentric worldview. We discuss how we implemented theoretical perspectives, research methods, and research ethical considerations. We found that we had to adapt the implementation of our research to be aligned with the norms and practices of the Vatsonga. Research ethical considerations are highlighted as an important step towards fostering indigenised research on the continent. In addition, we propose the dissemination of research findings to include indigenous communities where the research has been conducted. This should be done through community meetings or workshops as the African people follow an oral-based tradition of knowledge transmission. The paper concludes by highlighting the need for African literature to guide researchers in conducting research studies in indigenous African communities.